The end of the day [compact disc, unabridged] - Clegg, Bill (Simon & Schuster Audio, 2020)
A retired widow in rural Connecticut wakes to an unexpected visit from her childhood best friend whom she hasn't seen in forty-nine years. A man arrives at a Pennsylvania hotel to introduce his estranged father to his newborn daughter and finds him collapsed on the floor of the lobby. A sixty-seven-year-old taxi driver in Kauai receives a phone call from the mainland that jars her back to a traumatic past. These seemingly disconnected lives come together as half-century-old secrets begin to surface.